IDENTIFIKASI LOKASI PENGEMBANGAN AGROPILITAN KABUPATEN GUNUNG KIDUL - Darmadi Darmadi (Jurnal Dinamika Sosial Ekonomi, 2005)
The objective of this research is to identify location development of agropolitan area matching with the potentive to be center development of agropolitan area and policy of agricultural sector of Gunung Kidul District specially program development of agropolitan. Center development of agropolitan of Gunung Kidul determined from chosendistrict as location development of agropolitan, in this case District of Karangmojo. Determination of countryside as the center in relying on assessment of resident potency, infrastructure, medium economic activity, agriculture activity, planology and also sectoral policyKey Words :Agropolitan, Identify, Location, Center development